European Approaches To Resolving Public Disputes Between Population And Him Countries In Cases Of Hybrid Occupation - Батанова, Людмила Олександрівна; Батанова, Л. О.; Батанова, Людмила Александровна; Batanova, Liudmyla O.; Бєлкін, Марк Леонідович; Бєлкін, М. Л.; Белкин, Марк Леонидович; Bielkin, Mark L.; Belkin, Mark; Юринець, Юлія Леонідівна; Юринець, Ю. Л.; Юринец, Юлия Леонидовна; et al. (IJSTR Publishing, 2020)
In today‘s conditions of the world globalization, the occupation of separate territories became one of the threats to states. At the same time forms of this occupation acquire new manifestations, which contributed to the origin of such a concept as "hybrid occupation". Due to the inability of an injured state to control the occupied territories, its citizens face the problems of their legal rights, freedoms, and interests implementation. This fact leads to their appeals to national and international courts against their country (bodies of state power) with the requirements to ensure their constitutional rights. This article, based on legal methods of analysis and comparison, examines the decisions of the European Court of Human Rights on disputes of citizens who have become victims of a hybrid occupation with countries such as Turkey, Cyprus, Azerbaijan, Armenia, Moldova and Ukraine. Thus, the purpose of the research was formulated - to summarize the approaches and legal positions of the European Court of Human Rights in resolving disputes regarding the enforcement of human rights in territories that are actually controlled by hostile states (in cases of hybrid occupation). The research methodology is based on the methods of documentary analysis and synthesis, comparative analysis, objective truth, which al lowed us to systematically trace and generalize the position of the European Court of Human Rights on this issue. For the study we used the texts of five decisions of the European Court of Human Rights on this issue, which apply to all the hot spots in Europe. As a result of the legal comparison of the European Court of Human Rights decisions with norms of the Ukrainian legislation, conclusions about the conformity of national law with the practice of international justice have been made. Also, the position is asserted that the liability for the material or non-material harm inflicted to a country as a result of its territories hybrid occupation has to be held on a country-invader in accordance with the principles and norms of International Law.

У сучасних умовах світової глобалізації окупація окремих територій стала однією з загроз державам. Водночас форми цієї окупації набувають нових проявів, що сприяло виникненню такого поняття, як "гібридна окупація". Через нездатність потерпілої держави контролювати окуповані території, її громадяни стикаються з проблемами реалізації своїх законних прав, свобод та інтересів. Цей факт призводить до їх звернення до національних та міжнародних судів проти своєї країни (органів державної влади) з вимогами щодо забезпечення їх конституційних прав. Ця стаття, заснована на юридичних методах аналізу та порівняння, розглядає рішення Європейського суду з прав людини щодо суперечок громадян, які стали жертвами гібридної окупації в таких країнах, як Туреччина, Кіпр, Азербайджан, Вірменія, Молдова та Україна. Таким чином, була сформульована мета дослідження - узагальнити підходи та правові позиції Європейського суду з прав людини при вирішенні суперечок щодо забезпечення прав людини на територіях, які фактично контролюються ворожими державами (у випадках гібридної окупації). Методологія дослідження базується на методах документального аналізу та синтезу, порівняльного аналізу, об'єктивної істини, що дозволило систематично відстежувати та узагальнювати позицію Європейського суду з прав людини з цього питання. Для дослідження ми використали тексти п’яти рішень Європейського суду з прав людини з цього питання, які стосуються усіх гарячих точок Європи. В результаті юридичного порівняння рішень Європейського суду з прав людини з нормами українського законодавства зроблено висновки про відповідність національного законодавства практиці міжнародного правосуддя. Також стверджується, що відповідальність за матеріальну або нематеріальну шкоду, заподіяну країні в результаті гібридної окупації її територій, повинна нести країна-загарбник відповідно до принципів та норм міжнародного права.

В современных условиях мировой глобализации оккупация отдельных территорий стала одной из угроз государствам. В то же время формы этой оккупации приобретают новые проявления, что способствовало возникновению такого понятия, как "гибридная оккупация". Из-за неспособности потерпевшего государства контролировать оккупированные территории, ее граждане сталкиваются с проблемами реализации своих законных прав, свобод и интересов. Этот факт приводит к их обращениям в национальные и международные суды против своей страны (органов государственной власти) с требованиями по обеспечению их конституционных прав. Эта статья, основанная на юридических методах анализа и сравнения, рассматривает решения Европейского суда по правам человека в спорах граждан, ставших жертвами гибридной оккупации в таких странах, как Турция, Кипр, Азербайджан, Армения, Молдова и Украина. Таким образом, была сформулирована цель исследования - обобщить подходы и правовые позиции Европейского суда по правам человека при решении споров по обеспечению прав человека на территориях, которые фактически контролируются враждебными государствами (в случаях гибридной оккупации). Методология исследования базируется на методах документального анализа и синтеза, сравнительного анализа, объективной истины, что позволило систематически отслеживать и обобщать позицию Европейского суда по правам человека по этому вопросу. Для исследования мы использовали тексты пяти решений Европейского суда по правам человека по этому вопросу, которые касаются всех горячих точек Европы. В результате юридического сравнения решений Европейского суда по правам человека с нормами украинского законодательства сделаны выводы о соответствии национального законодательства практике международного правосудия. Также утверждается, что ответственность за материальный или нематериальный ущерб, причиненный стране в результате гибридной оккупации ее территорий, должна нести страна-захватчик в соответствии с принципами и нормами международного права.
Belkin M. European Approaches To Resolving Public Disputes Between Population And Him Countries In Cases Of Hybrid Occupation / M. Belkin, Ju. Iurynets, L. Batanova, K. Marych, G. Ierko // International Journal of Scientific & Technology Research. – V. 9 (1). – IJSTR Publishing, 2020. – P. 3838-3843.
Keywords: international law; international liability; human rights; hybrid occupation; national law; міжнародне право; міжнародна відповідальність; права людини; гібридна окупація; національне право; международное право; международная ответственность; права человека; гибридная оккупация; национальное право; Research Subject Categories::LAW/JURISPRUDENCE